1993
DOI: 10.1002/art.1780361209
|View full text |Cite
|
Sign up to set email alerts
|

Generalized osteoarthritis associated with increased insulin‐like growth factor types i and ii and transforming growth factor β in cortical bone from the iliac crest. possible mechanism of increased bone density and protection against osteoporosis

Abstract: Objective. To investigate whether growth factors stored in bone might explain the increased bone density and resistance to osteoporosis in generalized osteoarthritis.Methods. Levels of insulin-like growth factor (IGF) types I and I1 and transforming growth factor (TGFP) were measured in extracts of cortical bone from the iliac crest obtained at necropsy from subjects with or without osteoarthritis of the hands.Results. Concentrations of IGF-I, IGF-11, and TGFP were significantly higher in extracts of bone powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
128
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(139 citation statements)
references
References 48 publications
9
128
1
1
Order By: Relevance
“…Other studies showed a higher presence of bone growth factors in patients with DISH, and suggested a possible relevant role for those substances in the pathogenesis of the disease [30]. The finding may be confirmed by the presence of hyperostosis in some disorders with a high production of growth factors [7]. In fact, DISH is a diffuse systemic condition in which it is likely that both mechanical and local factors act on the propensity to deposit new bone.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies showed a higher presence of bone growth factors in patients with DISH, and suggested a possible relevant role for those substances in the pathogenesis of the disease [30]. The finding may be confirmed by the presence of hyperostosis in some disorders with a high production of growth factors [7]. In fact, DISH is a diffuse systemic condition in which it is likely that both mechanical and local factors act on the propensity to deposit new bone.…”
Section: Discussionmentioning
confidence: 84%
“…More recently it has been suggested that systemic metabolic factors may be involved in the new bone growth that characterises the disease. On the other hand, the presence of such systemic factors has been hypothesised also in primary osteoarthritis (OA); in fact, increased skeletal concentrations of insulin-like growth factor I, insulin-like growth factor II and transforming growth factor b have been considered as possible mechanisms that increase bone density in OA [7]. Although DISH is often considered to be a variant of OA, diarthrodial joints are not involved, intervertebral joints spaces are preserved and apophyseal joints appear to be normal.…”
Section: Introductionmentioning
confidence: 99%
“…Gevers and Dequeker also showed elevated serum osteocalcin levels in women with hand OA, and elevated osteocalcin in cortical bone explants [24]. Moreover, levels of growth factors such as insulin-like growth factor (IGF)-1 and -2 and transforming growth factor (TGF)-β1 are also higher in samples of iliac crest bone of patients with OA [25]. Considering that this bone is a non-weight-bearing site and at some distance from joints, this would suggest a generalised dysfunction in bone metabolism.…”
Section: Correlation Between In Vivo Findings In Animals and Human Oamentioning
confidence: 91%
“…A role of bone has also been speculated, in that obesity increases subchondral bone stiffness, making bone less adept at coping with impact loads (7,8). The increased stiffness of bone may subsequently redistribute a greater force across the underlying articular cartilage, increasing its vulnerability to degenerative changes (9).…”
mentioning
confidence: 99%